Strengthening Pesantren Economic Development Through Kopontren Al-Fithrah - Muhammad Syauqi (Journal of Islamic Banking, 2024)
This study aims to analyze the strategic role of Kopontren Al-Fithrah in strengthening the pesantren economy through the provision of Islamic financial services, professional business management, and a community-based empowerment model. Using a descriptive qualitative approach with a case study design, the research collected data through interviews, observations, and documentation to capture the economic dynamics within the pesantren environment. The findings reveal that Kopontren Al-Fithrah functions as the central driver of the pesantren’s economic ecosystem by expanding access to capital, creating business opportunities, and fostering an entrepreneurial culture among students and surrounding communities. Professionally managed business units contribute to the pesantren’s financial independence, while the cooperative’s impact is evident in the improved welfare of its members and the strengthening of socio-economic networks that support institutional sustainability. These results highlight the significant contribution of pesantren cooperatives in building a community-based economy that is adaptive, resilient, and competitive.